Website Aesthetic in Millenial’s Customer Experience on Satisfaction and Impulse Buying: EWOM as Moderator - Rina Anindita; Dbora Putri Perdana (Media Ekonomi dan Manajemen, 2022)
Various online website marketplaces attract consumers to experience a good and visually pleasing shopping experience, especially for the young age group in generation Y or millennials. This study was made to explore the effect of online shopping experience in terms of aesthetics on customer satisfaction and impulse buying with eWOM as moderation. Through this study, there is a goal to contribute in explaining the importance of website aesthetics in the consumer shopping experience by adding eWOM for the millennial group which can affect customer satisfaction and impulse buying. The research was conducted by collecting data through a survey using a questionnaire distributed online. Data were analyzed using Structural Equation Model- Partial Least Square (SEM-PLS). The findings in this study are first, good aesthetics can directly increase customer satisfaction, and second, aesthetics influence impulse buying. The research implication, so that companies can set up the eWOM area as an active and positive means for customers to exchange and share their own opinions about the online shopping experience.